2016
DOI: 10.3389/fimmu.2016.00411
|View full text |Cite
|
Sign up to set email alerts
|

NFAT2 Regulates Generation of Innate-Like CD8+ T Lymphocytes and CD8+ T Lymphocytes Responses

Abstract: Nuclear factor of activated T cells (NFAT) 2 null mutant mice die in utero of cardiac failure, precluding analysis of the role of NFAT2 in lymphocyte responses. Only the NFAT2−/−/Rag-1−/− chimeric mice model gave insight into the role of NFAT2 transcription factor in T lymphocyte development, activation, and differentiation. As reports are mainly focused on the role of NFAT2 in CD4+ T lymphocytes activation and differentiation, we decided to investigate NFAT2’s impact on CD8+ T lymphocyte responses. We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…after thymic selection 30 . Taken together, our NGS and ChIP seq data on the genome-wide gene control by NFATc1 in CD8 + T cells confirm and extend the data by Pachulec et al 11 on the NFATc1-mediated control of IFNγ production in CD8 + T cells.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…after thymic selection 30 . Taken together, our NGS and ChIP seq data on the genome-wide gene control by NFATc1 in CD8 + T cells confirm and extend the data by Pachulec et al 11 on the NFATc1-mediated control of IFNγ production in CD8 + T cells.…”
Section: Discussionsupporting
confidence: 90%
“…The latter showed a decrease in their cytotoxicity (Supplementary Fig. 3 a), similar to the findings published by Pachulec et al 11 for Nfatc1 −/− CD8 + T cells.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…NFAT is a transcription factor that is predominantly regulated by activation and the subsequent translocation from the cytoplasm to the nucleus. NFAT activation/regulation is measured by total NFAT2 protein/mRNA expression levels (45,46). The results demonstrated that the ARB VAL attenuated the HG-induced increase of TRPC6 and NFAT in podocytes in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 95%